Graphite composite negative electrode active material and preparation method and application thereof

By covering the surface of the graphite negative electrode material with a coating of polymer, fluorine-containing organolithium compounds and porous carbon particles, the insufficient performance of lithium-ion batteries under fast charging and low temperature conditions is solved, and higher first-time efficiency and high-temperature storage performance are achieved.

CN119864407AActive Publication Date: 2025-04-22SICHUAN KUNTIAN NEW ENERGY TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510130180.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-22
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

The graphite anode material of existing lithium-ion batteries exhibits the problems of low efficiency and insufficient performance for the first time under fast charging and low temperature conditions. Especially under high temperature storage conditions, the repeated formation of SEI film consumes lithium ions, reducing the high temperature storage performance.

Method used

The graphite composite negative electrode active material is used to improve the material's physical and chemical structure and ion and electron conduction pathways by covering the surface of the graphite by polymers, fluorine-containing organolithium compounds and porous carbon particles.

Benefits of technology

It significantly improves the fast charging and low-temperature performance of graphite negative electrode materials, improves the first-time efficiency and high-temperature storage performance, and enhances the structural stability of the material and the transmission network efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864407A_ABST
    Figure CN119864407A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery electrode materials, and provides a graphite composite negative electrode active material and a preparation method and application thereof, and the graphite composite negative electrode active material comprises graphite and a coating layer coating the surface of the graphite; and the coating layer comprises the following components: a polymer, a fluorine-containing organic lithium compound and porous carbon particles. According to the technical scheme, the problems of insufficient quick charging performance and low-temperature performance of the graphite negative electrode material in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery electrode materials, and in particular to a graphite composite negative electrode active material and a preparation method and application thereof. Background Art

[0002] At present, the fast-charging negative electrode materials used in lithium-ion batteries are mainly artificial graphite, which mainly improves fast charging and low-temperature performance by coating soft carbon or hard carbon on the surface of the material. There is a problem of low initial efficiency, and under high-temperature storage conditions, the repeated formation of SEI film consumes lithium ions and reduces high-temperature storage performance, resulting in low initial efficiency; the reason for the poor fast-charging performance and low-temperature performance of graphite negative electrode materials is that the consumption of lithium ions during the charging and discharging process causes the diffusion rate of lithium ions to slow down. Although some researchers have improved the initial efficiency and rate performance of the material by coating the surface of the material with inorganic lithium salt compounds, the improvement in the low-temperature performance of the material is not large. The reason is that although the diffusion coefficient of lithium ions at low temperatures is improved compared with graphite under low-temperature conditions, the improvement is not large.

[0003] For example, publication number CN114335460A discloses a fast-charging graphite composite material and a preparation method thereof. The graphite composite material includes an inner shell and an outer shell. The outer shell includes an inorganic lithium salt, carbon nanotubes and a remainder of amorphous carbon. The inner core includes porous graphite and a solid electrolyte. Although the fast charging performance is improved, the low-temperature performance of the material and its initial efficiency are not improved much.

[0004] For another example, a Chinese patent document with publication number CN115954455A discloses a method for preparing a graphite composite negative electrode material, which includes: hydrothermal reaction of a silver ammonia solution and a porous graphite solution to obtain a silver-doped graphite composite material; uniformly dispersing an aluminum salt solution and the silver-doped graphite composite material, filtering and sintering to obtain an alumina-coated silver-doped graphite composite material; uniformly dispersing the alumina-coated silver-doped graphite composite material, an amorphous carbon source, an inorganic lithium compound and a conductive agent in an organic solvent, spray drying and carbonizing to obtain the graphite composite negative electrode material.

[0005] Although there are many ways to modify graphite in existing technologies, research on the fast charging performance and low-temperature performance of graphite negative electrode materials is still not sufficient, and there is still much room for improvement in performance. Summary of the invention

[0006] The present invention provides a graphite composite negative electrode active material and a preparation method and application thereof, which solves the problems of insufficient fast charging performance and low temperature performance of graphite negative electrode materials in the related art.

[0007] The technical solution of the present invention is as follows: The present invention provides a graphite composite negative electrode active material, comprising graphite and a coating layer coated on the surface of the graphite; The coating layer comprises a polymer, a fluorine-containing organic lithium compound, and porous carbon particles; The structural formula of the fluorine-containing organic lithium compound is: ; In the formula, the R group is a hydrocarbon group containing a F substituent.

[0008] As a further technical solution, the R group is a fluorine-substituted C1~C3 alkyl group, preferably, the R group is a perfluorinated C1~C3 alkyl group; The polymer includes one or more of epoxy water-based resin, polyurethane resin, water-soluble phenolic resin and water-soluble polyester resin.

[0009] As a further technical solution, the mass ratio of the porous carbon particles, the polymer, the fluorine-containing organic lithium compound, and the graphite is 1-10:1-15:0.5-10:100; Preferably, the mass ratio of the porous carbon particles, the polymer, the fluorine-containing organic lithium compound, and the graphite is 3-5:5-10:0.5-6:100.

[0010] As a further technical solution, the porous carbon particles are porous carbon particles modified with lithium and titanium.

[0011] As a further technical solution, the method for preparing the porous carbon particles comprises the following steps: mixing a carbon source, a coupling agent, an organic template, and an organic lithium compound for pre-reaction, and carbonizing the mixture to obtain porous carbon particles.

[0012] As a further technical solution, the mass ratio of the carbon source, coupling agent, organic template and organic lithium compound is 100:1~5:1~5:1~5.

[0013] As a further technical solution, the carbon source includes a carbohydrate substance, and the carbohydrate substance includes one or more of sucrose, glucose, β-dextrin or lactose; The coupling agent is a titanium-based coupling agent; The titanium-based coupling agent includes one or more of isopropyl tris(dioctyl pyrophosphate acyloxy) titanate, tetraisopropyl di(dioctyl phosphite acyloxy) titanate and bis(dioctyl pyrophosphate ester) ethylene titanate; The organic template includes one or more of polystyrene microspheres, sodium laurate, and polyvinyl pyrrolidone; The organic lithium compound is one or more of lithium stearate, lithium octadecanoate, lithium acetate, lithium acetate, lithium benzoate, lithium oxalate, and lithium oxalate; An organic solvent is also added during the pre-reaction; The organic solvent includes one or more of cyclohexane, n-hexane, carbon tetrachloride or N-methylpyrrolidone.

[0014] As a further technical solution, the pre-reaction temperature is 25-150°C and the time is 1-6h; Preferably, the temperature of the pre-reaction is 50-120°C; The carbonization treatment is carried out in nitrogen or an inert gas.

[0015] The present invention also provides a method for preparing the graphite composite negative electrode active material, comprising the following steps: The porous carbon particles, polymer, fluorine-containing organic lithium compound and graphite are mixed in liquid phase and dried to obtain a graphite composite negative electrode active material; The liquid phase mixed solvent includes water; The drying includes spray drying.

[0016] The present invention also proposes the use of the graphite composite negative electrode active material or the graphite composite negative electrode active material prepared by the preparation method in a lithium ion battery.

[0017] In the present invention, a carbon source, a coupling agent, an organic template, and an organic lithium compound are firstly used for pre-reaction and carbonization, and porous carbon particles co-doped with lithium formed by pyrolysis of an organic lithium compound and a titanium-based coupling agent and TiO2 are prepared, and the modified porous carbon particles are further modified with the fluorine-containing organic lithium compound and other components to achieve synergy, optimize the physicochemical structure of the material, improve the ion and electron conduction pathways of the material, optimize the transmission network and efficiency, reduce defects and expansion, improve structural stability, and further improve the low temperature and fast charging performance of the graphite negative electrode material.

[0018] The working principle and beneficial effects of the present invention are: In the present invention, a new graphite composite negative electrode active material is provided, including graphite and a coating layer coated on the surface of the graphite. The components of the coating layer contain polymers, fluorine-containing organic lithium compounds, and porous carbon particles. Based on the combination of the physical and chemical characteristics of the materials, it can achieve synergy and significantly improve the fast charging, low temperature and other properties of the graphite negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0020] Figure 1 This is a SEM image of the graphite composite negative electrode active material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1 The method for preparing a graphite composite negative electrode material comprises the following steps: S1. Add 100 g sucrose, 3 g isopropyl tri(dioctyl pyrophosphate) titanate, 3 g polystyrene microspheres, and 3 g lithium stearate to 800 g cyclohexane and disperse them evenly, transfer them to a high-pressure reactor, react at 80° C. for 3 h, filter, and vacuum dry the resulting residue at 80° C. for 24 h, and carbonize at 1150° C. for 3 h to obtain porous carbon particles. S2. Mix 8 g of water-soluble epoxy resin and 300 g of 2 wt% lithium trifluoromethanesulfonate (LiSO3CF3) aqueous solution, add 3 g of porous carbon particles and 100 g of artificial graphite, disperse them evenly by ultrasonication, and then spray dry to obtain a graphite composite negative electrode active material.

[0023] Example 2 The method for preparing a graphite composite negative electrode material comprises the following steps: S1. Add 100 g of glucose, 1 g of tetraisopropyl di(dioctylphosphite) titanate, 1 g of sodium laurate, and 1 g of lithium octadecanoate to 500 g of n-hexane and disperse evenly, transfer to a high-pressure reactor, react at 50° C. for 6 h, filter, and vacuum dry the resulting residue at 80° C. for 24 h, and carbonize at 800° C. for 6 h to obtain porous carbon particles. S2. Mix 5 g of polyurethane resin and 50 g of 1 wt% aqueous solution of lithium perfluorobutanesulfonate (LiSO3C4F9), add 5 g of porous carbon particles and 100 g of artificial graphite, disperse them evenly by ultrasonication, and then spray dry to obtain a graphite composite negative electrode active material.

[0024] Example 3 The method for preparing a graphite composite negative electrode material comprises the following steps: S1. Add 100 g lactose, 5 g bis(dioctyloxypyrophosphate)ethylene titanate, 5 g polyvinyl pyrrolidone, and 5 g lithium acetate to 1000 g carbon tetrachloride and disperse evenly, transfer to a high-pressure reactor, react at a temperature of 120° C. for 1 h, filter, and vacuum dry the obtained residue at 80° C. for 24 h, and carbonize at 1300° C. for 1 h to obtain porous carbon particles; S2, 10g of water-soluble phenolic resin and 5wt% of lithium perfluorohexane sulfonate (LiSO3C6F 13) were mixed with 40 g of an aqueous solution, 3 g of porous carbon particles were added, and 100 g of artificial graphite was ultrasonically dispersed uniformly, and then spray-dried to obtain a graphite composite negative electrode active material.

[0025] Example 4 The difference between this embodiment and embodiment 1 is that isopropyl tri(dioctyl pyrophosphate) titanate and lithium stearate are not added.

[0026] Example 5 The difference between this example and Example 1 is that isopropyl tri(dioctyl pyrophosphate) titanate is replaced by titanium dioxide.

[0027] Example 6 The only difference between this embodiment and embodiment 1 is that lithium stearate is replaced by lithium hydroxide.

[0028] Comparative Example 1 The only difference between this comparative example and Example 1 is that lithium trifluoromethanesulfonate (LiSO3CF3) is not added.

[0029] Comparative Example 2 The difference between this comparative example and Example 1 is that lithium trifluoromethanesulfonate (LiSO3CF3) is replaced by compound II; The structural formula of compound II is as follows: .

[0030] 1. SEM test The graphite composite negative electrode active material prepared in Example 1 was subjected to SEM testing, and the results are as follows: Figure 1 As shown. Figure 1 It can be seen that the material presents a partially spherical structure with a particle size between 8 and 12 µm.

[0031] 2. Physical and chemical properties test The tap density and specific surface area of ​​the graphite composite negative electrode active materials in Examples 1 to 6 and Comparative Examples 1 to 2 were tested according to the test method in the standard GB / T 24533-2019 "Graphite Negative Electrode Materials for Lithium Ion Batteries", and the OI value of the powder material was tested by XRD, and the diffusion coefficient was tested by GITT. The test results are shown in Table 1.

[0032] Table 1 Physical and chemical properties test

[0033] It can be seen from Table 1 that the diffusion coefficient, tap density and OI value of the graphite composite negative electrode materials prepared in Examples 1-3 are significantly better than those in Examples 4-5 and Comparative Examples 1-2.

[0034] 3. Button battery test The graphite composite negative electrode active materials prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were assembled into button batteries according to the following method: The negative electrode was prepared by mixing graphite composite negative electrode active material, CMC, SRR, and SP (wherein the mass ratio of graphite composite negative electrode active material, CMC, SRR, and SP was 95:1.5:2.5:1), and assembled into a button cell with lithium sheet, electrolyte, and separator in a glove box with argon and water content less than 0.1ppm. Among them, the separator was celegard 2400; the electrolyte was a solution of LiPF6, in which the concentration of LiPF6 was 1 mol / L, and the solvent was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) mixed in a weight ratio of 1:1.

[0035] The button cells were tested for their performance using a blue battery tester. The test conditions were: 0.1C rate charge and discharge, voltage range 0.05-2V, and 3 cycles. The discharge capacity was then tested at 1C, and the 1C / 0.1C rate performance, cycle performance (25±3℃, 0.2C / 0.2C, 100 weeks) and low temperature capacity retention (-20℃ capacity / 25℃ capacity) were calculated. The test results are shown in Table 2.

[0036] Table 2 Button battery test

[0037] It can be seen from Table 2 that the discharge capacity, first efficiency and low temperature performance of the button-type battery prepared by using the graphite composite negative electrode material of Examples 1 to 3 are significantly higher than those of Comparative Examples 1 to 2. The experimental results show that the graphite composite active material of the present invention can make the battery have good discharge capacity, first efficiency and low temperature performance. The reason is that the graphite composite active material of Examples 1 to 3 has a higher diffusion coefficient, which improves the low temperature performance.

[0038] 4. Soft pack battery performance test The graphite composite negative electrode active material prepared in each case was used as the negative electrode active material to prepare the negative electrode (the formula was: the mass ratio of active material, CMC, SRR, SP was 95:1.5:2.5:1, and the positive electrode active material ternary material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2) to prepare the positive electrode (the positive electrode material formula is the active material, PVDF, SP mass ratio of 95:5:5), electrolyte and separator are assembled into a 5Ah soft-pack battery.

[0039] The separator is celegard 2400, and the electrolyte is LiPF6 solution (the solvent is a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 is 1.1 mol / L). The prepared soft-pack battery is subjected to HPPC rate performance; HPPC rate performance: 3C pulse charging and 4C pulse discharge were performed, and the charging DCR under different SOC conditions (5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%) was tested. The test results are shown in Table 3.

[0040] Table 3 Soft pack battery performance test

[0041] It can be seen from Table 3 that the DCR of the soft-pack battery examples 1-3 prepared from the obtained graphite composite materials is significantly lower than that of the comparative examples 1-2.

[0042] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A graphite composite negative electrode active material, characterized in that: It comprises graphite and a coating layer coated on the surface of the graphite; The coating layer comprises a polymer, a fluorine-containing organic lithium compound, and porous carbon particles; The structural formula of the fluorine-containing organic lithium compound is: ; In the formula, the R group is a hydrocarbon group containing a F substituent.

2. The graphite composite negative electrode active material according to claim 1, characterized in that: The R group is a fluorine-substituted C1~C3 alkyl group, preferably, the R group is a perfluorinated C1~C3 alkyl group; The polymer includes one or more of epoxy water-based resin, polyurethane resin, water-soluble phenolic resin and water-soluble polyester resin.

3. The graphite composite negative electrode active material according to claim 1, characterized in that: The mass ratio of the porous carbon particles, the polymer, the fluorine-containing organic lithium compound, and the graphite is 1-10:1-15:0.5-10:100; Preferably, the mass ratio of the porous carbon particles, the polymer, the fluorine-containing organic lithium compound, and the graphite is 3-5:5-10:0.5-6:

100.

4. The graphite composite negative electrode active material according to claim 3, characterized in that: The porous carbon particles are porous carbon particles modified with lithium and titanium.

5. The graphite composite negative electrode active material according to claim 4, characterized in that: The method for preparing porous carbon particles comprises the following steps: mixing a carbon source, a coupling agent, an organic template and an organic lithium compound for pre-reaction, and carbonizing to obtain porous carbon particles.

6. The graphite composite negative electrode active material according to claim 5, characterized in that: The mass ratio of the carbon source, the coupling agent, the organic template and the organic lithium compound is 100:1-5:1-5:1-5.

7. The graphite composite negative electrode active material according to claim 5, characterized in that: The carbon source includes a carbohydrate, and the carbohydrate includes one or more of sucrose, glucose, β-dextrin or lactose; The coupling agent is a titanium-based coupling agent; The titanium-based coupling agent includes one or more of isopropyl tris(dioctyl pyrophosphate acyloxy) titanate, tetraisopropyl di(dioctyl phosphite acyloxy) titanate and bis(dioctyl pyrophosphate ester) ethylene titanate; The organic template includes one or more of polystyrene microspheres, sodium laurate, and polyvinyl pyrrolidone; The organic lithium compound is one or more of lithium stearate, lithium octadecanoate, lithium acetate, lithium acetate, lithium benzoate, lithium oxalate, and lithium oxalate; An organic solvent is also added during the pre-reaction; The organic solvent includes one or more of cyclohexane, n-hexane, carbon tetrachloride or N-methylpyrrolidone.

8. The graphite composite negative electrode active material according to claim 5, characterized in that: The pre-reaction temperature is 25-150°C and the time is 1-6h; Preferably, the temperature of the pre-reaction is 50-120°C.

9. The method for preparing a graphite composite negative electrode active material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The porous carbon particles, polymer, fluorine-containing organic lithium compound and graphite are mixed in liquid phase and dried to obtain a graphite composite negative electrode active material.

10. Use of the graphite composite negative electrode active material according to any one of claims 1 to 8 or the graphite composite negative electrode active material prepared by the preparation method according to claim 9 in a lithium ion battery.

Citation Information

Patent Citations

  • Fast-charging graphite composite material and preparation method thereof

    CN114335460A

  • Graphite composite negative electrode material, preparation method thereof, negative electrode plate and lithium battery

    CN115954455A

  • Composite cathode material and preparation method thereof and lithium ion battery

    CN112271280A

  • High-energy-density fast-charging graphite composite material and preparation method thereof

    CN118993057A

  • Graphite coated with porous carbon and lithium secondary battery comprising the same as anode active material

    KR1020160148392A